Localización geográfica y sectores de inversión: factores decisivos en el desempeño de las multinacionales mexicanas durante la crisis - Basave Kunhardt, Jorge (2013)
During the global crisis, Foreign Direct Investment (FDI) has withdrawn from developed economies and has substantially increased in emerging and transitional economies. In this scenario, Mexican MNEs have been spreading during the last four years, after starting their internationalization two decades ago. In this paper, we show that the relationship between two factors— economic sector and geographical location of FDI — explains the difference in outcome of corporate operations during the crisis. While positive results have been found regarding investments in Latin America and Asia, less favorable results are registered in investments in Europe and the United States. These findings modify the theoretical approach on the “location determinants” of FDI. Our sources are enterprise's websites and direct surveys applied during the last four years for a sample of 20 of the largest MNEs in Mexico.